The main predictors of seasonal blood pressure changes in patients with stable arterial hypertension in Moscow - G. F. Andreeva; V. M. Gorbunov; Ya. N. Koshelyaevskaya; E. V. Platonova (Рациональная фармакотерапия в кардиологии)
Aim. To determine the main socio- demographic, psychological, hemodynamic and meteorological predictors of seasonal blood pressure (BP) increase in the cold season in patients with stable arterial hypertension (AH) in Moscow.   Material and methods. The study was conducted at the National Medical Research Center for Therapy and Preventive Medicine from 1997 to 2009. It involved patients with hypertension without severe concomitant diseases requiring regular therapy. At the first and second visits, psychological status (PS) and quality of life (QL) were assessed, daily blood pressure monitoring (ABPM) was performed. All procedures were performed after washout period (3-5 days). Visits were carried out in different months of the same year, and the difference in daily ambient temperatures between the first and second visits was 5 °C or more. PS was assessed using the Mini- Mult test (Russian short version of MMPI questionnaire, Minnesota Multiphasic Personality Inventory), QL — using the "General Well- Being Questionnaire" (GWBQ). The severity of the seasonal blood pressure increase (ΔBP) with a in ambient temperature decrease and indicators was calculated as the difference betweenthe BP levels that were recorded in the colder and warmer seasons. A multivariate regression analysis was performed to assess the relationships between the ΔBP severity and initial hemodynamic data, socio- demographic indicators, and psychological characteristics of AH patients.   Results. Data from 137 patients with stable AH (77 (56 %) women, 60 (40 %) men) were analyzed. The average age was 55.7 ± 0.8 years, the AH duration was 11.9 ± 0.8 years, the height — 167.3 ± 0.7 cm, weight — 81.1 ± 1.2 kg, mass index body (BMI) — 28.9 ± 0.4 kg/m2. The initial blood pressure during ABPM were: 1) average daytime systolic BP (SBPd) 144.7 ± 1.4 mm Hg, nighttime (SBPn) — 126.0 ± 1.3 mm Hg; 2) average daytime diastolic BP (DBPd) — 91.6 ± 0.8 mm Hg, nighttime (DBPn) — 75.1 ± 0.8 mm Hg. After regression analysis, the following seasonal BP increase predictors in the cold season were found: 1) for SBPd — DBPd — 5 scale scores of the QL questionnaire; 3) for DBPn — diastolic white coat effect (WCEd). Several seasonal BP decrease predictors were found: 1) for DBPd — systolic WCE (WCEs) and body mass index (BMI).   Conclusion. The main hemodynamic predictors of the BP seasonal changes were WCE level. The psychological component of QL was a DBPd seasonal increase predictor, and BMI was a DBPd seasonal decrease predictor in the cold season.